2012
DOI: 10.1080/03630242.2012.717595
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Meaning of a Woman with a Hysterectomy Among Mexican Physicians and Women

Abstract: The psychological meaning of women who have had a hysterectomy, and attitudes toward them, were explored in 121 Mexican gynecologists, 155 women who had undergone a hysterectomy, and 115 women who had not had a hysterectomy. The surveys were completed between January and May 2011. Both groups of women defined a woman who had had a hysterectomy using words with positive meanings (healthy, happy, reassured, and complete), as well as words with negative meanings (sad, incomplete, and irritable). However, the part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A recent survey in Mexico mapping attitudes to hysterectomy among three different groups: gynaecologists, women who had been through hysterectomy and women who had not had hysterectomy, concluded that although there were negative characteristics (sadness, incompleteness, irritableness) involved, there were mostly positive meanings relating to hysterectomy (Marván, Catillo-Loez, & Ehrenzweig, 2012 ). Interestingly, the group in the Mexican study tending to attach the most negative meanings to hysterectomy was the group of women who had not undergone the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey in Mexico mapping attitudes to hysterectomy among three different groups: gynaecologists, women who had been through hysterectomy and women who had not had hysterectomy, concluded that although there were negative characteristics (sadness, incompleteness, irritableness) involved, there were mostly positive meanings relating to hysterectomy (Marván, Catillo-Loez, & Ehrenzweig, 2012 ). Interestingly, the group in the Mexican study tending to attach the most negative meanings to hysterectomy was the group of women who had not undergone the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Hysterectomy is a very common gynecological surgery with approximately 50,000 women recipients each year in the United States alone. Since the uterus plays a special social, sexual, and psychological role, diseases and surgeries that are related with the uterus can bring forth very high incidence rate of psychiatric disorders [1,2]. With the change in the socio-biomedical model, change of the psychological status of women before and after hysterectomy has become a focus of study in the psychosomatic medicine [3,4].…”
Section: Introductionmentioning
confidence: 99%